Catheter-Based Renal Denervation Reduces Atrial Nerve Sprouting and Complexity of Atrial Fibrillation in Goats. (April 2015) - Linz, Dominik; van Hunnik, Arne; Hohl, Mathias; Mahfoud, Felix; Wolf, Milan; Neuberger, Hans-Ruprecht; Casadei, Barbara; Reilly, Svetlana N.; Verheule, Sander; Böhm, Michael; Schotten, Ulrich
<x xml:space="preserve">Abstract</x> Background— Atrial fibrillation (AF) leads to structural and neural remodeling in the atrium, which enhances AF complexity and perpetuation. Renal denervation (RDN) can reduce renal and whole-body sympathetic activity. Aim of this study was to determine the effect of sympathetic nervous system modulation by RDN on atrial arrhythmogenesis. Methods and Result— Eighteen goats were instrumented with an atrial endocardial pacemaker lead and a burst pacemaker. Percutaneous catheter-based RDN was performed in 8 goats (RDN-AF). Ten goats undergoing a sham procedure served as control (SHAM-AF). AF was induced and maintained by burst pacing for 6 weeks. High-resolution mapping was used to record epicardial conduction patterns of the right and left atrium. RDN reduced tyrosine hydroxylase-positive sympathetic nerve staining and resulted in lower transcardiac norepinephrine levels. This was associated with reduced expression of nerve growth factor-β, indicating less atrial nerve sprouting. Atrial endomysial fibrosis content was lower and myocyte diameter was smaller in RDN-AF. Median conduction velocity was higher (75±9 versus 65±10 cm/s, P=0.02), and AF cycle length was shorter in RDN-AF compared with SHAM-AF. Left atrial AF complexity (4.8±0.8 fibrillation waves/AF cycle length versus 8.5±0.8 waves/AF cycle length, P=0.001) and incidence of breakthroughs (2.0±0.3 versus 4.3±0.5 waves/AF cycle length, P=0.059) were lower in RDN-AF compared with SHAM-AF. Blood pressure was normal and not significantly different between the groups. Conclusions— RDN reduces atrial sympathetic nerve sprouting, structural alterations, and AF complexity in goats with persistent AF, independent of changes in blood pressure.